THERMAL SENSING OF HIGHORI TEMPERATURE SOLAR INSTRUMENTS, SOLAR PHOTOELECTRIC ENERGY (American Journal of Pedagogical and Educational Research, 2023)
This concertation in the article the sun water heater heat sensitive high temperature the sun of devices feel the heat. the sun photoelectric energy about data seeing developed.